High-sensitivity C-reactive protein concentrations among patients with and without diabetes in a multiethnic population of Singapore: CREDENCE Study - Dalan R (Dove Medical Press, 2010)
Rinkoo Dalan1, Michelle Jong1, Siew-Pang Chan4,5, Robert Hawkins2, Robin Choo6, Brenda Lim1, May L Tan3, Melvin KS Leow1,61Department of Endocrinology, 2Department of Laboratory Medicine, 3Health Enrichment Centre, Tan Tock Seng Hospital, Singapore; 4School of Business, SIM University, Singapore; 5Faculty of Health Sciences, La Trobe University, Australia; 6Singapore Institute for Clinical Sciences, Brenner Centre for Molecular Medicine, SingaporeObjectives: To determine whether high-sensitivity C-reactive protein (hs-CRP) concentrations differ between Chinese, Malays, and Indians with and without type 2 diabetes mellitus and to look for an association with demographic, metabolic and therapeutic variables.Methods: Phase 1: We retrieved records of 50 Chinese, 51 Malay, and 67 Indian individuals who had routine health screening blood tests. Phase 2: We recruited 111 Chinese, 68 Malays, and 67 Indians with type 2 diabetes mellitus and measured their hs-CRP in addition to standard laboratory tests.Results: Phase 1: The median hs-CRP was 0.6 mg/L (0.2–6.2) in Chinese, 1.2 mg/L (0.2–7.9) in Malays, and 1.9 mg/L (0.2–10.0) in Indians. The Indians had higher hs-CRP compared to Chinese (P < 0.05) when adjusted for age, sex, body mass index (BMI), lipids, blood pressure, and smoking, and a significant correlation was seen between female sex, smoking status, fasting glucose and triglyceride concentration, and hs-CRP in all three ethnicities. Phase 2: The median hs-CRP was 1.2 mg/L (0.2–9.9) in Chinese, 2.2 mg/L (0.2–9.0) in Malays, and 2.3 mg/L (0.2–9.8) in Indians. Indians had higher hs-CRP when compared to Chinese (P < 0.05) and a significant correlation was seen between BMI, female gender, diabetes, and the use of metformin and hs-CRP in all three ethnicities (P < 0.05) when adjusted for the above variables and use of aspirin, angiotensin-converting enzyme inhibitor/angiotensin receptor blockers (ACE-I/ARB), statin, metformin, rosiglitazone, sulfonylurea, glinides, acarbose, and insulin.Conclusion: hs-CRP concentrations are significantly higher in Indians compared to the Chinese (in both the diabetic and nondiabetic individuals) after adjustment for the various demographic, metabolic, and therapeutic variables.Keywords: C-reactive protein, ethnicity, diabetes mellitus, cardiovascular disease